2014
DOI: 10.1097/rlu.0b013e31827a216b
|View full text |Cite
|
Sign up to set email alerts
|

Dual Tracer Functional Imaging of Gastroenteropancreatic Neuroendocrine Tumors Using 68Ga-DOTA-NOC PET-CT and 18F-FDG PET-CT

Abstract: Ga-DOTA-NOC PET-CT seems to be superior to F-FDG PET-CT for imaging GEP-NETs. However, their role seems to be complementary because combination of Ga-DOTA-NOC PET-CT and F-FDG PET-CT in such patients helps demonstrate the total disease burden and segregate them to proper therapeutic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 26 publications
(29 reference statements)
1
51
0
Order By: Relevance
“…Several studies have proven the superiority of 68 Ga-SMAs over conventional octreotide imaging with 111 In-diethylenetriaminepentaacetic acid ( 111 In-DTPA) and have reported high sensitivity values of up to 100% (11,12). 18 F-FDG PET/CT imaging has also been compared with SSTR imaging in several studies and has a variable sensitivity of 36%-84% in detecting GEPNETs (3,(13)(14)(15). However, the number 18 F-FDG PET/CT.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have proven the superiority of 68 Ga-SMAs over conventional octreotide imaging with 111 In-diethylenetriaminepentaacetic acid ( 111 In-DTPA) and have reported high sensitivity values of up to 100% (11,12). 18 F-FDG PET/CT imaging has also been compared with SSTR imaging in several studies and has a variable sensitivity of 36%-84% in detecting GEPNETs (3,(13)(14)(15). However, the number 18 F-FDG PET/CT.…”
Section: Discussionmentioning
confidence: 99%
“…The small size of NETs makes it difficult for conventional anatomic imaging to visualize the primary tumor or its metastases, given that these modalities are unable to depict specific endocrine features; consequently, the diagnostic accuracy of functional imaging is significantly higher than that of conventional imaging (7,(11)(12)(13)(14). 18 F-FDG PET/CT imaging has also been compared with 68 Ga-DOTA peptide imaging in several studies, which have shown it to have variable sensitivity in detecting NETs (15)(16)(17)(18)(19)(20)(21)(22). However, the presence of increased glucose in NETs highlights an increased propensity for invasion and metastasis, and 18 F-FDG PET/CT accordingly has higher sensitivity in delineating disease extent, especially in aggressive and high-grade tumors (23).…”
Section: Discussionmentioning
confidence: 99%
“…The present and future trend in oncological care heads towards personalizing treatments in order to reduce the side effects of current available therapies and individualizing management to each patient. And this is where the Nuclear Medicine Therapeutics is a cornerstone in achieving the objective [6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%